Empowering Start-Ups : The Impact of Business Incubation Centers in Delhi-NCR - Chahal, Nisha; Abhishek (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : This study aimed to assess the involvement of Business Incubation Centers in encouraging the growth and development of startups within the Delhi-NCR region. Furthermore, it also discussed the comprehensive support and resources provided by these incubators to emerging entrepreneurs, including mentoring, infrastructure, financial guidance, technical know-how, legal services, and networking opportunities. Methodology : Using statistical methods like frequency analysis, t-test, and analysis of variance (ANOVA), it gathered primary data from a sample of 100 respondents from 9 business incubation facilities in Delhi, Gurugram, and Noida. Findings : According to the research, respondents usually think that there is a greater chance of survival and growth for startups who enroll in incubation programs. The respondents identified the centers’ infrastructure, resources, and co-working space as being beneficial in lowering start-up expenses. Many of the participants also recognized the support incubators offer to start-up entrepreneurs in the form of insightful mentoring and advice. Practical Implications : In a nation like India, where unemployment is rising and the population is enormous, more business incubators ought to be supported. These business incubators fostered the development of startups and, consequently, the local entrepreneurial culture. Incubator operators, aspiring entrepreneurs, and government policymakers interested in starting up would find this study useful. Originality : This research primarily focused on the impact of business incubators in a specific region that has not been explored yet and discussed the role these centers play in empowering the young start-ups in a region.